Apparent digestibility of three diets in the Amiata breed donkey during lactation - Gatta, Domenico; Casini, Lucia; Magni, Livio; Liponi, Gian Battista (Italian journal of animal science, 2009)
The aim of the trial was to evaluate the apparent digestibility of three isonitrogenous and isocaloric diets for lactating donkeys: a diet with 8 kg of hay and 1.5 kg of commercial flaked mixed feed (CM) (Diet 1); a diet with 7 kg of hay and a 2.2 kg of CM (Diet 2) and a diet with 7 kg of hay, 1.5 kg of CM, 200 ml of corn oil and 0.2 kg of soybean meal (Diet 3). Four pluriparous donkeys (309±12 kg BW) at approximately 2-4 months of lactation were used. The trial was conducted according to a 3x3 Latin Square design with 1 or 2 subject per each cell. Feed and faeces samples were analysed for DM, OM, CP, EE, CF, NDF, ADF and gross energy. Acid insoluble ash was used as marker to calculate the apparent digestibility. The apparent digestibility of the main dietary components showed not significant differences among the three diets but generally they were lower in Diet 3. DM intakes of every diet exceeded the estimated energy requirement, whereas protein requirements were not significantly satisfied by Diet 1.